Semaglutide in the Treatment of Diabetes and Associated Obesity - Makuch, Rafal; Chrościcka , Alicja; Gała, Kamil; Czajka, Andrzej; Lenard, Paweł; Kucharski, Adam; Michalska, Sara; Pilarski, Konrad; Dewicka, Martyna; Wawrzyniak, Alicja Maria (Journal of Education, Health and Sport, 2024)
Introduction and objective: Diabetes represents one of the most significant healthcare challenges of the 21st century. The disease is frequently asymptomatic, with patients often remaining undiagnosed for extended periods and failing to seek assistance from healthcare professionals. A sedentary lifestyle, excessive caloric intake, and a lack of physical activity contribute to the development of obesity, which in turn leads to carbohydrate metabolism disorders. In this study, we will examine the relationship between diabetes and obesity, and discuss the drug semaglutide, which is used to treat type 2 diabetes and also promotes weight loss. Review methods: Review and summary of research studies available in open-source format on Google Scholar, PubMed. Abbreviated description of the state of knowledge: Numerous clinical studies have demonstrated the efficacy of semaglutide in improving lipid profiles and promoting weight loss. This effect is believed to be mediated by the drug’s ability to slow gastric emptying. It is evident that semaglutide, a glucagon-like peptide-1 (GLP-1) analogue, exerts a beneficial effect on carbohydrate parameters and helps to delay the occurrence of complications associated with diabetes. Summary: A review of clinical reports and conducted studies indicates that semaglutide has the potential to enhance parameters that directly or indirectly impact the quality of life of patients with diabetes. However, the utilisation of the aforementioned pharmaceutical is associated with adverse effects, which may impede patient-physician collaboration and potentially precipitate the development of new health complications in patients. One of the effects of semaglutide treatment is a reduction in appetite, which contributes to weight loss. This property of the drug makes it suitable for use in patients with excessive body weight.